Correlation of Serum Ferritin with Hematocrit in Children Infected with Dengue - I Nyoman Budi Hartawan; Made Yuliantari Dwi Astiti; I Wayan Gustawan; Ida Bagus Gede Suparyatha; Dyah Kanya Wati; Made Gede Dwi Lingga Utama; Siska Permanasari Sinardja; I Made Yullyantara Saputra; Putu Andrie Setiawan (Molecular and Cellular Biomedical Sciences, 2026)
Background: Dengue infection is a major global health concern in tropical and subtropical regions, especially among children, ranging from mild to severe disease with high morbidity and mortality. Although ferritin and hematocrit have prognostic value individually, their correlation in pediatric dengue remains underexplored. This study was conducted to determine the correlation between serum ferritin and hematocrit levels in children with dengue infection.Materials and methods: This cross-sectional study included 69 children with dengue infection. Data collected included age, sex, nutritional status, disease severity, and hematologic parameters. Blood samples were obtained from all participants, serum ferritin levels were measured using Chemiluminescent Microparticle Immunoassay (CMIA), while hematocrit was measured from whole blood using an automated hematology analyzer. Correlation was assessed using Pearson’s or Spearman’s rho test, followed by multiple linear regression analysis.Results: The mean age was 10.09±4.23 years old, with 52.2% male and 47.8% female participants. Nutritional status was 29% undernourished, 58% normal, and 13% overnourished. Mild dengue was observed (65.2%), while 34.8% had severe disease. The mean serum ferritin level was 4820.97±6327.75 ng/mL, and the mean hematocrit was 42.10±6.21%. Spearman’s Rho test showed significant moderate positive correlation between serum ferritin and hematocrit. Multiple linear regression analysis demonstrated that increased serum ferritin levels were significantly correlated with an increased hematocrit levels, whereas age, gender, nutritional status, and disease severity were not significantly associated.Conclusion: Serum ferritin levels were positively correlated with serum hematocrit levels in children infected with dengue, suggesting a potential role for ferritin as both an inflammatory marker and an indicator of hemoconcentration for early risk stratification. Keywords: dengue, ferritin, hematocrit, children